2020
DOI: 10.3390/bioengineering7040139
|View full text |Cite
|
Sign up to set email alerts
|

Instrumented Analysis of the Sit-to-Stand Movement for Geriatric Screening: A Systematic Review

Abstract: The Sit-to-Stand (STS) is a widely used test of physical function to screen older people at risk of falls and frailty and is also one of the most important components of standard screening for sarcopenia. There have been many recent studies in which instrumented versions of the STS (iSTS) have been developed to provide additional parameters that could improve the accuracy of the STS test. This systematic review aimed to identify whether an iSTS is a viable alternative to a standard STS to identify older people… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 48 publications
(45 reference statements)
1
14
1
Order By: Relevance
“…Previous studies have attempted to capture the dynamics of 5STS using different sensors such as accelerometers, motion capture devices, force plates, depth cameras, and RGB cameras. [18][19][20][26][27][28][29] Shukla et al 19) showed that a force plate or loadcell-embedded seat could more accurately capture 5STS than depth or RGB cameras, with a smaller mean error size compared to a human expert examiner. In the study, 19) the results of the phase-determination rule-based algorithm interpreting the time-weight curve of a loadcell-embedded chair were generally similar, although researchers adopted a percent cut-off value to define phases rather than the absolute weight value as used in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies have attempted to capture the dynamics of 5STS using different sensors such as accelerometers, motion capture devices, force plates, depth cameras, and RGB cameras. [18][19][20][26][27][28][29] Shukla et al 19) showed that a force plate or loadcell-embedded seat could more accurately capture 5STS than depth or RGB cameras, with a smaller mean error size compared to a human expert examiner. In the study, 19) the results of the phase-determination rule-based algorithm interpreting the time-weight curve of a loadcell-embedded chair were generally similar, although researchers adopted a percent cut-off value to define phases rather than the absolute weight value as used in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Among the various tools used to assess the physical performance of lower extremities, the five times sit-to-stand test (5STS) is one of the most commonly used tests owing to its advantages in clinical implementation. 18 ) The test can be performed in clinical environments with restricted time and space. 19 ) 5STS is included in the consensus definition for sarcopenia, either as a separate test (≥12 seconds for impaired physical performance) or as a component of the Short Physical Performance Battery (SPPB) score (with scores ≤9 indicating impaired physical performance).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several linear kinematic parameters have been found to differentiate pathological and non-pathological STS, such as vertical, mediolaterial and anteroposterior acceleration, anteroposterior jerk, and vertical linear velocity (Millor et al, 2014 ). Velocity and acceleration measures during STS have shown potential in geriatric screening as well (Shukla et al, 2020 ). There are also some clinically relevant angular kinematic parameters such as knee extensor velocity and trunk tilt (Millor et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%